Mechanisms of ukrainian state support of innovations before and after the war - Novik, I. O.; Zhurba, Yevheniia Valentynivna (Національний технічний університет "Харківський політехнічний інститут", 2023)
Today, the national economy is underinvested in the country's investment and innovation sector, which leads to a downturn in production and a reduction in the investment capacity of market participants and the state. Only a scientifically substantiated and highly functional investment policy of the state has the potential to improve the prevailing situation in Ukraine. This article is intended to analyze the analysis of the mechanisms of state support for innovations in the world and in Ukraine in the past, and to propose the development of possible methodological and scientific-practical recommendations for improving the mechanism of development of state support for innovations in the country in the former peaceful and post-war period. The issue of researching the mechanisms of state support for innovations has always been important and relevant for the country's economy as a whole, as well as for individual enterprises and research institutions. To assist in supporting innovation in the most effective way, the state can use the following mechanisms: providing financial support, creating incubators and accelerators, developing research institutions, creating regulatory incentives, attracting investment, training and supporting young entrepreneurs, funding research, creating technology parks, tax incentives, introducing legislative incentives, and developing international cooperation.

Сьогодні національна економіка недоотримує інвестиції в інвестиційно-інноваційну сферу, що призводить до спаду виробництва та зниження інвестиційної спроможності суб'єктів ринку і держави. Лише науково обґрунтована та високофункціональна інвестиційна політика держави здатна покращити ситуацію, що склалася в Україні. Метою даної статті є аналіз механізмів державної підтримки інновацій у світі та в Україні в минулому, а також запропонувати розробку можливих методологічних та науково-практичних рекомендацій щодо вдосконалення механізму розвитку державної підтримки інновацій в країні в колишній мирний та післявоєнний період. Питання дослідження механізмів державної підтримки інновацій завжди було важливим і актуальним як для економіки країни в цілому, так і для окремих підприємств та науково-дослідних установ. Для того, щоб сприяти підтримці інновацій найефективнішим способом, держава може використати наступні механізми: надання фінансової підтримки, створення інкубаторів і акселераторів, розвиток науково-дослідних інститутів, створення регуляторних пільг, залучення інвестицій, навчання та підтримка молодих підприємців, фінансування наукових досліджень, створення технологічних парків, податкові пільги, введення законодавчих стимулів, розвиток міжнародного співробітництва.
Механізми державної підтримки інновацій в Україні до та після війни
Keywords: the development of investments and innovations; innovations; government support; development; розвиток інвестицій та інновацій; інновації; державна підтримка; розвиток